Spectrum-based pushover analysis for the quick seismic demand estimation of reinforced concrete shear walls. (October 2020) - Liu, Yang; Kuang, J.S.; Huang, Qunxian; Guo, Zixiong; Wang, Xueying
Abstract: In the design of medium- and high-rise buildings, the reinforced concrete (RC) shear wall structure is widely used to resist seismic loading. Thus, accurately predicting the seismic demand of this structural form becomes particularly important. However, existing multi-mode pushover analysis methods are mainly applied to predicting seismic demands of frame structures, while few attentions have been paid on other structural forms. In this paper, by revising the equation for predicting the overall roof displacement, the spectrum-based pushover analysis (SPA) of RC shear wall structures for the fast prediction of the seismic demand is presented. The accuracy of the SPA method in the fast prediction of seismic demands of RC shear wall structures was investigated through a case study on two representative RC shear wall buildings. The impact of the input ground motions (IGM) scaling target spectra on the accuracy of the SPA method was studied by selecting and scaling IGMs with the target spectra being the ASCE design spectra and conditional mean spectra. Seismic demands computed by the SPA method, the nonlinear response time history analysis (NLRHA), and the other two advanced methods of multi-mode pushover analysis were compared. It is indicated from the comparison of the seismic demands that the SPA method predicted seismic demands of RC shear wall structures with outstanding and consistent accuracy. Therefore, the SPA method can be considered as a solution for the fast seismic demand prediction of RC shear wall structures for different regions, where different target spectra are used as the seismic intensity representatives.